Building the case for the calcitonin receptor as a viable target for the treatment of glioblastoma. (December 2020) - Gupta, Pragya; Furness, Sebastian G. B.; Bittencourt, Lucas; Hare, David L.; Wookey, Peter J.
Researchers are actively seeking novel targeted therapies for the brain tumour glioblastoma (GBM) as the mean survival is less than 15 months. Here we discuss the proposal that the calcitonin receptor (CT Receptor), expressed in 76–86% of patient biopsies, is expressed by both malignant glioma cells and putative glioma stem cells (GSCs), and therefore represents a potential therapeutic target. Forty-two per cent (42%) of high-grade glioma (HGG; representative of GSCs) cell lines express CT Receptor protein. CT Receptors are widely expressed throughout the life cycle of organisms and in some instances promote apoptosis. Which of the common isoforms of the CT Receptor are predominantly expressed is currently unknown, but a functional response to cell stress of the insert-positive isoform is hypothesised. A model for resistant malignancies is one in which chemotherapy plays a direct role in activating quiescent stem cells for replacement of the tumour tissue hierarchy. The putative role that the CT Receptor plays in maintenance of quiescent cancer stem cells is discussed in view of the activation of the Notch–CT Receptor–collagen V axis in quiescent muscle (satellite) stem cells. The pharmacological CT response profiles of four of the HGG cell lines were reported. Both CT responders and non-responders were sensitive to an immunotoxin based on an anti-CT Receptor antibody. The CALCR mRNA exhibits alternative splicing commonly associated with cancer cells, which could result in the atypical pharmacology exhibited by CT non-responders and an explanation of tumour suppression. Due to the inherent instability of CALCR mRNA, analysis of CT Receptor protein in patient samples will lead to improved data for the expression of CT Receptor in GBM and other cancers, and an understanding of the role and activity of the splice variants. This knowledge will aid the effective targeting of this receptor for treatment of GBM.